Research techniques and instruments in research activity - Saras Zapata, Edgar (2023)
The quality of a research work depends, mainly, on the adequate choice of the design and development of the techniques, as well as the instruments that will be used. Once the identification of the problem, the determination of the variables and the conceptualization have been carried out, it will proceed to its decomposition into dimensions, indicators and items, a fundamental activity to find its essence. This item construction procedure requires cognitive domain of the categories to be used; For this, it is necessary to create a theoretical framework, based on existing documentation. Then proceed with the design and development of the instrument, which will necessarily go through an assessment process to determine its construct validity, content, item analysis, confirmatory analysis, and reliability. The instruments generally respond to the type, level and design of the investigation, considering the number of subjects that constitute the sample or units of analysis. The next stage will consist of data collection and its pertinent organization, product of the various sources used by the researcher. The sources are resources that contain data and refer to facts or situations, documents or records that the researcher uses to access the information. These are basically primary or secondary. A data or information collection instrument is a methodological resource that is materialized in a set of reagents, expressed in a device or format (printed or digital) that is used to collect, record, or store the relevant aspects of the study collected from the sources. suitable. Hernández et al (2014) agree when stating that it is a "resource used by the researcher to record information or data about the variables he has in mind" (p.199).